Differential microbial composition in parasitic vs. questing ticks based on 16S next-generation sequencing - Zhang, Lin; Han, Jing; Zhou, Qi; He, Zhen; Sun, Shi-Wei; Li, Rui; Li, Rui-Shan; Zhang, Wen-Kai; Wang, Yu-Hua; Xu, Lin-Li; Lu, Zhen-Hua; Shao, Zhong-Jun (Frontiers in Microbiology, 2023)
As tick-borne diseases rise to become the second most prevalent arthropod-transmitted disease globally, the increasing investigations focus on ticks correspondingly. Factors contributed to this increase include anthropogenic influences, changes in vertebrate faunal composition, social-recreational shifts, and climatic variation. Employing the 16S sequence method in next-generation sequencing (NGS) allows comprehensive pathogen identification in samples, facilitating the development of refined approaches to tick research omnidirectionally. In our survey, we compared the microbial richness and biological diversity of ticks in Wuwei City, Gansu province, differentiating between questing ticks found in grass and parasitic ticks collected from sheep based on 16S NGS method. The results show Rickettsia, Coxiella, and Francisella were detected in all 50 Dermacentor nuttalli samples, suggesting that the co-infection may be linked to specific symbiotic bacteria in ticks. Our findings reveal significant differences in the composition and diversity of microorganisms, with the Friedmanniella and Bordetella genera existing more prevalent in parasitic ticks than in questing ticks (p < 0.05). Additionally, the network analysis demonstrates that the interactions among bacterial genera can be either promotive or inhibitive in ticks exhibiting different lifestyles with the correlation index |r| > 0.6. For instance, Francisella restrains the development of six other bacteria in parasitic ticks, whereas Phyllobacterium and Arthrobacter enhance colonization across all tick species. By leveraging NGS techniques, our study reveals a high degree of species and phylogenetic diversity within the tick microbiome. It further highlights the potential to investigate the interplay between bacterial genera in both parasitic and questing ticks residing in identical habitat environments.